2013
DOI: 10.1002/jat.2969
|View full text |Cite
|
Sign up to set email alerts
|

Use of the mouse ear vesicant model to evaluate the effectiveness of ebselen as a countermeasure to the nitrogen mustard mechlorethamine

Abstract: Previous studies in this and other laboratories have demonstrated that ebselen (EB-1), an organoselenium compound, spares cells from mechlorethamine (HN2) toxicity in vitro. In the present study, the hypothesis that EB-1 will reduce dermal toxicity of HN2 in vivo is put forward and found to have merit. Using the mouse ear vesicant model (MEVM), HN2, applied topically, showed a dose-dependent effect upon ear swelling and thickness 24 h after treatment; whereas tissue injury consistent with vesication was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…These ions can react with organic and inorganic anions, amino groups, and sulphide groups in biological systems (Wheeler, 1962), causing severe damage even at very low concentrations. To study the cutaneous damage from SM, NM and other analogues, various animal models have been used (Chauhan et al, 1993, Cowan et al, 1993, Dabrowska et al, 1996, Dorandeu et al, 2011, Lomash et al, 2011, Lulla et al, 2013, Papirmeister, Gross, 1985, Riviere et al, 1995, Sharma, Vijayaraghavan, 2008, Wormser, 1991). However, at present, mechanistic aspects of the injury are still poorly understood and the lack of suitable models hampers the development and screening of effective therapeutic and prophylactic compounds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These ions can react with organic and inorganic anions, amino groups, and sulphide groups in biological systems (Wheeler, 1962), causing severe damage even at very low concentrations. To study the cutaneous damage from SM, NM and other analogues, various animal models have been used (Chauhan et al, 1993, Cowan et al, 1993, Dabrowska et al, 1996, Dorandeu et al, 2011, Lomash et al, 2011, Lulla et al, 2013, Papirmeister, Gross, 1985, Riviere et al, 1995, Sharma, Vijayaraghavan, 2008, Wormser, 1991). However, at present, mechanistic aspects of the injury are still poorly understood and the lack of suitable models hampers the development and screening of effective therapeutic and prophylactic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…NM has crosslinking property similar to SM, is commercially available and due to the containment facility required for SM, has been used by several groups to study vesicant--induced injury (Hardej and Billack, 2007, Lulla, Reznik, 2013, Pino and Billack, 2008, Sharma et al, 2010a). SKH-1 hairless mice, which has been found to be suitable for experiments with SM and SM analogues, was used as the animal model in this study These studies showed that NM exposure (3.2 mg/mouse) in mice led to severe cutaneous injury, and that NM-related clinical, histopathological, and immunohistochemical effects were similar to those observed following SM-exposure in humans and other animal models (Dorandeu, Taysse, 2011, Jain et al, 2011, Jain et al, 2014a, Pal et al, 2009, Tewari-Singh et al, 2011, Tewari-Singh et al, 2014a, Tewari-Singh et al, 2013, Tewari-Singh et al, 2014b, Tewari-Singh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Mechlorethamine (HN2) is a prototype nitrogen mustard (NM) that shares a similar structure and toxicity profile with the chemical warfare agent sulfur mustard (SM) (Korkmaz et al, 2006; Shakarjian et al, 2010). HN2 is widely used as a surrogate to study and mimic the effects of SM under laboratory conditions (Composto et al, 2018; Lulla et al, 2014; Malaviya et al, 2015; Sunil et al, 2011; Tumu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such irritants add to the edema induced by the mustard. Casillas’ MEVM has become the standard in vivo measurement of antimustard therapeutics . We have used the Casillas MEVM to obtain all the measurements of inflammation suppression reported herein …”
mentioning
confidence: 99%
“…Casillas' MEVM has become the standard in vivo measurement of antimustard therapeutics. 15,16 We have used the Casillas MEVM to obtain all the measurements of inflammation suppression reported herein. 6,7,27 While Casillas found edema suppression following treatment with known COX inhibitors, established protease inhibitors, TRPV1 inhibitors, and several other categories of inhibitors, no evidence of summative effects was observed.…”
mentioning
confidence: 99%